2000
DOI: 10.1038/sj.ijo.0801195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperglycaemia and hyperinsulinaemia on plasma amino acid levels in obese subjects with normal glucose tolerance

Abstract: OBJECTIVE: To investigate the effects of hyperglycaemia and hyperinsulinaemia on amino acid disposal in human obesity. DESIGN: Four sequential experimental conditions: (1) overnight fasting; (2) hyperglycaemia with hyperinsulinaemia (2 h hyperglycaemic clamp at 11 mmolal); (3) hyperglycaemia with basal insulin (1 h hyperglycaemic clamp during somatostatin infusion), (4) hyperglycaemia with resuming hyperinsulinaemia (1 h hyperglycaemic clamp after somatostatin discontinuation). SUBJECTS: Seven non-obese and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
6
0
2
Order By: Relevance
“…We found elevated plasma BCAAs in ob/ob mice and high-fat diet-induced obesity in mice and in Zucker fatty rats, in agreement with previous reports in obese humans and Zucker fatty rats (4,5,11,12,37,46,48,49,52,56). These elevations were associated with reductions in the activity or amount of enzymes involved in the early steps of BCAA metabolisms in selective tissues, including liver and fat.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We found elevated plasma BCAAs in ob/ob mice and high-fat diet-induced obesity in mice and in Zucker fatty rats, in agreement with previous reports in obese humans and Zucker fatty rats (4,5,11,12,37,46,48,49,52,56). These elevations were associated with reductions in the activity or amount of enzymes involved in the early steps of BCAA metabolisms in selective tissues, including liver and fat.…”
Section: Discussionsupporting
confidence: 80%
“…obesity; mitochondrial branched chain amino acid transaminase; branched chain keto acid dehydrogenase; branched chain keto acid dehydrogenase kinase; ob/ob mice; Zucker rats; bariatric surgery; humans PLASMA CONCENTRATIONS of branched-chain amino acids (BCAAs) are elevated in humans and animal models of obesity (4,11,12,31,37,46,48,52,56). Although the plasma levels of other amino acids may also change in obesity, the rises in the BCAAs are of particular interest because they appear to have unique obesity-related effects.…”
mentioning
confidence: 99%
“…Adipose tissue has been suggested to be quantitatively important for whole-body BCAA catabolism [32], [37], [38] and in obesity a consistent finding has been decreased gene expression of BCAA catabolic enzymes in adipose tissue [27], [30], [33], [39]. In contradistinction, some studies, e.g., [21], but not all, e.g., [14], have reported increased Leu oxidation in obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, using [1- 13 C]-Leu and gas-chromatography mass spectrometry (GC-MS), elevated protein turnover and proteolysis in obese humans has been reported [14], [15], [16], [17], [18], [19]. However this too has not always been observed [20], [21] and seems inconsistent with the findings that aminoacidemia in lean animals and in obesity activates mTOR kinase activity. In lean animals, such signaling by BCAAs increases protein synthesis and inhibits muscle protein degradation as measured by changes in 3-methylhistidine (3-MeHis) [10], [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…The rapamycin-sensitive pathway via mammalian target of rapamycin (mTOR) is known to be a target activated by the nutrient, which controls the mammalian translation machinery via activation of p70 S6 kinase (S6K1) and inhibition of the eukaryotic initiation factor (eIF)4E inhibitor, 4E-BP1 (also known as PHAS-I) (15)(16)(17)(18). In addition to the physiological role of amino acids, previous studies have shown that fasting plasma amino acid concentrations are elevated both in rodents and human subjects with obesity (19,20). Thus, the chronic elevation of amino acid concentrations appears to be associated with the pathological state including the insulin resistance syndrome (19).…”
mentioning
confidence: 98%